Comparison of two long-term gestagen regimens in the management of recurrent vulvovaginal candidiasis: A pilot study - Špaček, Jiří; Kestřánek, Jan; Jílek, Petr; Leško, Daniel; Plucnarová, Silvie; Buchta, Vladimír (Mycoses, 2017)
Vulvovaginal candidiasis (VVC) is a hormonal-dependent infection but in contrast to sporadic VVC, therapy of recurrent vulvovaginal candidiasis (RVVC) is still unsolved. Long-term administration of medroxyprogesterone acetate was evaluated for the management of RVVC. Overall, 20 patients were treated with Depo-Provera; 14 patients were treated with Provera. Gestagen therapy was evaluated based on visual analogue scale (VAS), the frequency of attacks, the side effects of gestagens and the consumption of antifungals. There was a reduced symptomatology in both of the groups and substantial reduction in antifungal drug consumption during the second year of gestagen use. Twenty-four patients (70.6%) evaluated their condition regarding the vulvovaginal area as improvement (VAS decrease of 3-5 points). Five patients (14.7%) mentioned minimal or no improvement. Further, a number of antifungal drug-treated episodes dropped dramatically during the study period. Both regimes provided similar results, but five patients from the Depo-Provera group had to withdraw from gestagen therapy. Gestagen supplementation ameliorated the quality of life for the majority of patients with RVVC and suggested a potential role in the management of this syndrome, even if beneficial effect was evident after longer application, and some patients met with side effects that led to an interruption of therapy.
Keywords: recidiva; Candidiasis, Vulvovaginal; Humans; antifungální látky; Quality of Life; Female; mladý dospělý; dospělí; management nemoci; Progestins; Prospective Studies; lidé; recurrent vulvovaginal candidiasis; kvalita života; Medroxyprogesterone Acetate; pilotní projekty; Pilot Projects; kandidóza vulvovaginální; progestiny; Adult; vizuální analogová stupnice; ženské pohlaví; Antifungal Agents; Adolescent; Visual Analog Scale; Recurrence; Young Adult; hormonal imbalance; quality of life; medroxyprogesteronacetát; vulvovaginal discomfort; čas; prospektivní studie; gestagens; Disease Management; Time; mladiství; Candida